Corrosion Assessment of Pre-corrosion Concrete Specimens using Acoustic Emission Technique - Ahmad Zaki; Zainah Ibrahim (Institute for Research and Community Services, Institut Teknologi Bandung, 2021)
The acoustic emission (AE) technique is known as a non-destructive testing (NDT) method, which is effective for assessing corrosion in concrete structures. This study aims to utilize the AE technique, for the assessment of pre-corroded concrete specimens, which are under load testing. Experiments were carried out on small-scale pre-corroded specimens, which were subjected to monotonic loading. The results showed that the majority of the beam specimens failed with shear cracks. Three AE parameters, namely acoustic emission hits, as well as the RA and AF values, were also used, in order to assess the flexure behaviour of the pre-corroded beam specimens. These experiments helped to understand the flexural behaviour of pre-corroded specimens, which were under a loading test, via the use of the AE technique.